2009
DOI: 10.1128/jvi.02670-08
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus Infection Induces Autophagy in both Cultured Cells and Human Skin Vesicles

Abstract: When grown in cultured cells, varicella-zoster virus (VZV) forms many aberrant light particles and produces low titers. Various studies have explored the reasons for such a phenotype and have pointed to impaired expression of specific late genes and at lysosomal targeting of egressing virions as possible causes. In the studies presented here, we report that the autophagic degradation pathway was induced at late time points after VZV infection of cultured cells, as documented by immunoblot analysis of the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 45 publications
10
80
1
Order By: Relevance
“…Thus, we have greatly extended earlier findings in which we detected autophagosomes in a biopsy sample from one case of human zoster (47). In other words, we have demonstrated that autophagy occurs during both primary VZV infection and VZV reactivation within the skin vesicle, the final site of virion assembly and envelopment.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Thus, we have greatly extended earlier findings in which we detected autophagosomes in a biopsy sample from one case of human zoster (47). In other words, we have demonstrated that autophagy occurs during both primary VZV infection and VZV reactivation within the skin vesicle, the final site of virion assembly and envelopment.…”
Section: Discussionsupporting
confidence: 68%
“…Effects of tunicamycin on autophagy in uninfected and VZVinfected cells. We previously described a prominent punctate LC3B staining pattern in VZV-infected MRC-5 cells compared with a diffuse pattern in uninfected cells (47). Here we show that the punctate pattern of LC3B immunoreactivity in VZV-infected MRC-5 cells was virtually identical to the punctate pattern seen in uninfected MRC-5 cells treated with tunicamycin ( Fig.…”
Section: Enumeration Of the Cellular Constituents Within A Vesiclesupporting
confidence: 64%
See 1 more Smart Citation
“…We had previously investigated VZV autophagic flux by measurement of stress-inducible intracellular p62/SQSTM1 protein levels in infected cells, and showed that VZV-induced autophagy was completed, leading to the degradation of p62/ SQSTM1 (15). To confirm and extend our observations, we measured autophagic flux by a traditional pulse-chase assay using radiolabeled amino acids.…”
Section: Discussionmentioning
confidence: 98%
“…In early experiments, we documented the presence of autophagosomes in skin vesicles from immunocompetent children with varicella or adults with herpes zoster (15,16). To confirm that the autophagy seen in the VZV-infected skin xenografts in SCID mice, which lack adaptive immune responses, recapitulated the response seen in human skin vesicles from children with varicella, we performed a direct comparison.…”
Section: Autophagy In Vzv-infected Human Skin Xenografts In the Scidmentioning
confidence: 99%